Analysis of carrier recombination dynamics in InGaN-based light-emitting diodes by differential carrier lifetime measurement. (7th April 2017) - Han, Dong-Pyo; Shim, Jong-In; Shin, Dong-Soo
Abstract: In this work, we investigate the carrier recombination dynamics in InGaN-based blue LED devices by analyzing the radiative and nonradiative carrier lifetimes as functions of driving current. To separate the radiative and nonradiative carrier lifetimes, we utilize the information on the internal quantum efficiency (IQE) and differential carrier lifetime. For comparative analysis, the characteristics of the IQE and electroluminescence spectrum are also used. Through measurements and analyses, we demonstrate that the saturation of the radiative recombination rate induced by the phase-space filling in the active volume triggers the increase in nonradiative recombination rate, thus leading to the efficiency droop.